Successfully integrating aged care services: a review of the evidence and tools emerging from a long-term care program - Stewart, Michael J. (Igitur publishing, 2013)
BACKGROUND: Providing efficient and effective aged care services is one of the greatest public policy concerns currently facing governments. Increasing the integration of care services has the potential to provide many benefits including increased access, promoting greater efficiency, and improving care outcomes. There is little research, however, investigating how integrated aged care can be successfully achieved. The PRISMA (Program of Research to Integrate Services for the Maintenance of Autonomy) project, from Quebec, Canada, is one of the most systematic and sustained bodies of research investigating the translation and outcomes of an integrated care policy into practice. The PRISMA research program has run since 1988, yet there has been no independent systematic review of this work to draw out the lessons learnt. METHODS: Narrative review of all literature emanating from the PRISMA project between 1988 and 2012. Researchers accessed an online list of all published papers from the program website. The reference lists of papers were hand searched to identify additional literature. Finally, Medline, Pubmed, EMBASE and Google Scholar indexing databases were searched using key terms and author names. Results were extracted into specially designed spread sheets for analysis. RESULTS: Forty-five journal articles and two books authored or co-authored by the PRISMA team were identified. Research was primarily concerned with: the design, development and validation of screening and assessment tools; and results generated from their application. Both quasi-experimental and cross sectional analytic designs were used extensively. Contextually appropriate expert opinion was obtained using variations on the Delphi Method. Literature analysis revealed the structures, processes and outcomes which underpinned the implementation. PRISMA provides evidence that integrating care for older persons is beneficial to individuals through reducing incidence of functional decline and handicap levels, and improving feelings of empowerment and satisfaction with care provided. The research also demonstrated benefits to the health system, including a more appropriate use of emergency rooms, and decreased consultations with medical specialists. DISCUSSION: Reviewing the body of research reveals the importance of both designing programs with an eye to local context, and building in flexibility allowing the program to be adapted to changing circumstances. Creating partnerships between policy designers, project implementers, and academic teams is an important element in achieving these goals. Partnerships are also valuable for achieving effective monitoring and evaluation, and support to ‘evidence-based’ policy-making processes. Despite a shared electronic health record being a key component of the service model, there was an under-investigation of the impact this technology on facilitating and enabling integration and the outcomes achieved. CONCLUSIONS: PRISMA provides evidence of the benefits that can arise from integrating care for older persons, particularly in terms of increased feelings of personal empowerment, and improved client satisfaction with the care provided. Taken alongside other integrated care experiments, PRISMA provides further evidentiary support to policy-makers pursuing integrated care programs. The scale and scope of the research body highlights the long-term and complex nature of program evaluations, but underscores the benefits of evaluation, review and subsequent adaptation of programs. The role of information technology in supporting integration of services is likely to substantially expand in the future and the potential this technology offers should be investigated and harnessed.